Does Increased Platelet Aggregation Have a Prognostic Value in the Deterioration of Background Diabetic Retinopathy? - Plu, G; Lecrubier, C; Scarabin, P Y; Baudoin, C; Samama, M; on behalf of the Damad Study Group (Thrombosis and Haemostasis, 1990)
Many case-control studies have suggested that increased platelet aggregation (PA) could be involved in the pathogenesis of diabetic microangiopathy. However, longitudinal data are needed to support this hypothesis. We consider here such an approach in the placebo group (93 diabetic patients) of a controlled clinical trial on the effect of PA inhibitors in the treatment of diabetic retinopathy (Damad program). We have measured spontaneous PA and PA induced by ADP, collagen and arachidonic acid before treatment and yearly during a 3-year period. The assessment of retinopathy was based on the changes in the number of microaneurysms present in the macular field as seen on fluorescein angiograms during follow-up. PA was estimated by maximal decrease in optical density. The lowest ADP concentration still able to induce irreversible aggregation was also determined. No significant correlations between any baseline PA measurements and end point criterion were found (all correlation coefficients lower than 0.20). No significant changes in mean PA were observed during follow-up. Within-subject variation of PA was markedly large accounting for 61% to 98% of the total variance of various measurements. Allowances for the main characteristics of diabetes made no substantial difference to the results. These negative findings can be partly attributed to the lack of reliability of PA tests. In our study, we conclude that PA tests are not useful measures for the prediction of evolution of background diabetic retinopathy.